INKUBATOR KOTA - Marcellus Rafi; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2019)
Social relation in human life fades subconsciously. Millennial which known for its tendency to always collaborate, is also not even try to synergize the compartmentalized way of life in a contrasted social-economic class. Even architects, most prefer to wrestle with fantastic designs rather than inovate the social interrelation. As a result, the city of Jakarta is filled with magnificent buildings with the principle of